Vulvovaginal Candidiasis and its Antifungal Susceptibility Pattern: Single center experience - Ruchi Rati; Jaya Patel; Suman Rishi (International Journal of Medical Research and Review, 2015)
Introduction: Candidiasis is the most common vaginal infection affecting about 70% of women. Our aim was isolation and identification of Candida from high vaginal swabs and in vitro antifungal activity of Fluconazole, Voriconazole, Nystatin, Amphotericin B.Materials and Methods: This study was carried out in NIMS Medical College, Jaipur during June 2013 to May 2014. The study group consisted of 100 women of reproductive age having symptomatic vaginal discharge, vulval purities or lower abdominal pain. High vaginal swabs were collected from each and processed by Gram Staining, culture on Sabroud’s dextrose agar & CHROM agar. Antifungal susceptibility was performed by disc diffusion method as per CLSI guidelines.Results: Vulvovaginal candidiasis accounted for 22 % of cases. Species distribution is as follows: C.albicans 12, C tropicalis 7, C krusei 2, C glabrata 1. Senstivity to Voriconazole was 91.6% for C albicans, 71.42 % for C.tropicalis, 50% for C.krusei. Senstivity to Fluconazole was seen in 91.6 % of C.albicans & 42.85 % of C.tropicalis. C. glabrata was resistant to both Voriconazole & Fluconazole. Senstivity to Amphotericin B was 75 % for C. albicans, 100 % for C.tropicalis, 100% for C.krusei & C. glabrata. Senstivity to Nystatin was 91.6% for C.albicans & 100% for C.tropicalis, C.krusei & C.glabrata.Conclusions: There is an increase in non-albicans Candida infection and few like C.krusei are intrinsically resistant to azoles. This signifies the need of species identification & antifungal susceptibility as a routine laboratory procedure in diagnosis of vaginal candidiasis.